Hsa_circ_0006834 represses intrahepatic cholangiocarcinoma proliferation through activating AMPK-mTOR pathway and autophagy via has-miR-637-NGFR network - Ji Wang; Xinyue Qi; Wangqian Zhao; Ziyan Hao; Kehan Wang; Yuting Li; Yue Wang; Yunshan Zhang (PLoS ONE, 2025)
Intrahepatic cholangiocarcinoma (iCCA) is a malignancy with difficult treatment and poor prognosis, whose pathogenesis could be associated with the expression patterns of circular RNAs (circRNAs). Here, we aim to investigate the effects and mechanism of hsa_circ_0006834 on iCCA proliferation. At first, hsa_circ_0006834 was proved to suppress iCCA cells proliferation and induce autophagy following the construction of hsa_circ_0006834 vector. And hsa_circ_0006834 is negatively linked with the proliferation, migration and invasion of iCCA cells through autophagy. Subsequently, RNA pull-down and dual-luciferase reporter assays were performed to validate the hsa_circ_0006834-has-miR-637-NGFR regulatory network. It was demonstrated by qPCR and Western blot that hsa_circ_0006834 stimulates the AMPK-mTOR pathway and triggers autophagy via NGFR after si-NGFR was synthesized and transfected into iCCA cells. Ultimately, after the successful knockdown of AMPK, the role of the AMPK-mTOR pathway in hsa_circ_0006834 regulating autophagy and proliferation was verified. Taken together, our findings revealed that hsa_circ_0006834 activates the AMPK-mTOR pathway and autophagy to suppress iCCA proliferation by has-miR-637-NGFR network, indicating the potential of hsa_circ_0006834 as a biomarker for iCCA diagnosis and therapy.